2022
DOI: 10.1055/a-1823-3604
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfonyl Halides from Disulfides or Thiols Using Sodium Hypochlorite Pentahydrate (NaOCl·5H2O) Crystals

Abstract: Synthesis of sulfonyl halides using sodium hypochlorite pentahydrate (NaOCl•5H2O) crystals was studied in detail, considering the reaction rate and yield of the desired product. NaOCl•5H2O reacted with disulfides or thiols in acetic acid to produce sulfonyl chlorides. The yields of the desired sulfonyl chlorides were enhanced when the reaction was performed in (trifluoromethyl)benzene under a CO2 atmosphere. The generation of hypochlomous acid (HOCl) was essential for both reactions. Similarly, sulfonyl bromid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…While the active species in the synthesis of sulfonyl chlorides and sulfonyl bromides in AcOH are HOCl and hypobromous acid (HOBr) (Scheme 4B), it was tested if hypofluorous acid (HOF) was generated from the reaction of NaOCl with AcOH in the presence of KF, which poses a significant challenge to believe. 49 Our results suggested that sulfonyl chloride 1 was initially produced from the reaction of disulfide 3 or thiol 4 with NaOCl•5H 2 O in acetic acids, and the resulting sulfonyl chloride 1 was then fluorinated by KF (Scheme 4C). This mechanism was further supported by the observation that both sulfonyl chloride 1a and sulfonyl fluoride 2a were formed after 1 h from the reaction of di-p-tolyl disulfide 3a with NaOCl• 5H 2 O and KF in AcOH, but after 17 h, only 1a was afforded (Scheme 4A).…”
Section: ■ Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…While the active species in the synthesis of sulfonyl chlorides and sulfonyl bromides in AcOH are HOCl and hypobromous acid (HOBr) (Scheme 4B), it was tested if hypofluorous acid (HOF) was generated from the reaction of NaOCl with AcOH in the presence of KF, which poses a significant challenge to believe. 49 Our results suggested that sulfonyl chloride 1 was initially produced from the reaction of disulfide 3 or thiol 4 with NaOCl•5H 2 O in acetic acids, and the resulting sulfonyl chloride 1 was then fluorinated by KF (Scheme 4C). This mechanism was further supported by the observation that both sulfonyl chloride 1a and sulfonyl fluoride 2a were formed after 1 h from the reaction of di-p-tolyl disulfide 3a with NaOCl• 5H 2 O and KF in AcOH, but after 17 h, only 1a was afforded (Scheme 4A).…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…This could be attributed to the mechanism of the active species' (HOCl) generation in the presence of AcOH, which is derived from the reaction of AcOH with NaOCl, thereby preventing the accumulation of NaCl and facilitating the progress of the reaction. 49 We further optimized the reaction using AcOH as the sole solvent and adjusted the other parameters for both disulfide 3 and thiol 4 substrates (refer to the Supporting Information). This approach afforded the corresponding sulfonyl fluoride 2a in a pure form, with yields of 73% (from 3a) and 75% (from 4a) following a one-pot protocol (Scheme 4A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Upon adding the acid species, there is an initial release of HCl, which gets regenerated in the early stages of the reaction. Subsequently, we assumed atmospheric CO 2 takes part in the reaction, 37 promoting the oxidative chlorination mechanochemical process, as illustrated in Scheme S1 in the ESI. † Other oxidative chlorination agents, such as TCIA and Ca(OCl) 2 , 38 provided compound 2a in lower yields (48% and 74%, respectively), corroborating the efficacy and the pivotal role played by NaOCl•5H 2 O in this mechanochemical process.…”
Section: Resultsmentioning
confidence: 99%
“…Several different mechanisms for the chlorosulfonylation of disulfides with dual-function reagents have been proposed. 18–20,29 Based on our experimental observations and existing literature studies for dual-function reagents, we attempted to propose a reaction mechanism for the chlorosulfonylation of disulfides. A plausible reaction mechanism with two alternative reaction pathways (A and B) is shown in Scheme 5.…”
Section: Resultsmentioning
confidence: 99%
“…17 Okada et al have also presented sodium hypochlorite pentahydrate (NaOCl·5H 2 O) as a solid and stable source of NaOCl for converting thiols and disulfides to their corresponding sulfonyl chlorides in the presence of acetic acid. 18…”
Section: Introductionmentioning
confidence: 99%